Does Chemically Modified Curcumin Control the Progression of Periodontitis? A Systematic Review - Dhaifullah E; Seayed HS; Mostafa D; Alharbi AMM; Alotaibi WM (Dove Medical Press, 2021)
Esam Dhaifullah,1 Hassan S Seayed,1 Diana Mostafa,1,2 Abdul Majeed M Alharbi,1 Waleed M Alotaibi1 1Department of Preventive Dental Sciences, Vision Colleges, Riyadh, Kingdom of Saudi Arabia; 2Clinical Periodontology Department, Faculty of Dentistry, Alexandria University, Alexandria, EgyptCorrespondence: Diana MostafaClinical Periodontology Department, Faculty of Dentistry, Alexandria University, Alexandria, EgyptEmail dr.dianamostafa@gmail.comBackground: Recently, pharmacologic approaches have been seen in utilizing matrix metalloproteinase inhibitors (MMP-I) to prohibit the destruction of connective tissue accompanied by erythrogenic inflammatory diseases such as periodontitis. However, curcumin characteristics have been described to be effective in reducing inflammatory mediators and matrix metalloproteinase (MMP). But, due to its poor solubility and bioavailability, a chemically modified curcumin (CMC 2.24) has been used.Objective: The purpose of this research is to review and analyze the animal attempts which investigate the impact of CMC2.24 on periodontitis.Materials and Methods: Our study was based on reviewing the English preclinical studies using CMC2.24 on an induced periodontal disease which were published up to 2020, only randomized control trials (RCTs) were included. Databases were used from electronic websites including PubMed, ScienceDirect, and Google scholar.Results: Seven experimental trials involving 162 rats and 8 dogs were included in the present systematic review. Six studies investigated LPS-induced experimental periodontitis, two of them worked on diabetes-associated periodontitis, while one study worked on naturally occurring periodontitis. All included studies revealed that CMC 2.24 reduced alveolar bone loss as well as inhibited the MMP.Conclusion: Collectively, we concluded that CMC 2.24 has significant implications in prohibiting the progression of bone loss.Keywords: chemically modified curcumin, matrix metalloproteinase, cytokines, periodontitis, CMC2.24